Evaluation of recombinant inbred lines based on morphological and biochemical parameters in Indian mustard (Brassica juncea L.) derived from Rohini × PBR-97 - Pramod K Rai,; Binay K Singh,; Supriya Ambawat,; Gajra Garg,; PD Meena,; Vijay V Singh, (Journal of Oilseed Brassica, 2026)
Among the rapeseed-mustard (Brassica spp.) group of crops Indian mustard (Brassica juncea L.) is theprincipal crop which accounts for approximately 85% of the total acreage under rapeseed-mustard. Here inthis study, a set of 225 recombinant inbred lines (RILs) developed through a cross between high yieldingcommercially released Indian mustard cultivars Rohini and PBR-97. were evaluated in F6:7 generation duringthe Rabi season of 2012 -2013 and data were recorded for various morphological and biochemical parameterssuch as plant height, main shoot length, fruiting zone length, siliqua length, seeds/siliqua, biological yield/plant,1000-seed weight, harvest index, seed yield/plant, oil content, and glucosinolates, fiber and phenol content.Significant genetic variation was observed among RILs for all the traits based on analysis of variance alongwith high genetic advance and high heritability for seed yield/plant, biological yield, 1000-seed weight, fibreand glucosinolates content. Seed yield/plant was found to be significantly and positively correlated with plantheight, biological yield, number of seeds/siliqua and 1000-seed weight. Among these RILs, 25 RILs wereidentified as highly promising RILs on the basis of seed yield/plant which can be further used for multilocationtesting for varietal release or used as parents in mustard breeding programs.